Breeding biology review of White-backed Stilt Himantopus melanurus in Brazil and a case study in the largest restinga protected area (Aves, Charadriiformes, Recurvirostridae) - Rodolfo Teixeira Frias; Lucas Rocha Melo Porto; Luciano Gomes Fischer; Patricia Luciano Mancini (Papéis Avulsos de Zoologia, 2022)
Abstract In Brazil, the White-backed Stilt Himantopus melanurus is distributed in the midwest, south and southeast but breeding information is scarce. In this study, species breeding information in the country was compiled from online platform (WikiAves, eBird) and literature. A case study describing nests and egg biometry were reported in Restinga of Jurubatiba National Park (RJNP), on the north cost of Rio de Janeiro state, as well potential threats to the species. Sampling was carried out in September and December 2018, monthly in 2019 and between January to March and September to December in 2020. Overall, 70 breeding records were compiled, between 1997 and November 2021, being 64 from WikiAves in all regions of Brazil, four records from eBird in São Paulo state (in 2021) and two records in literature (one from São Paulo state, in 2007 and one from Rio de Janeiro in 2012). In RJNP, 44 nests were identified being 34 active, with an average of 3.5 eggs per nest, and overall 118 eggs were measured. The main materials used to build the nests were the saltmarsh plant and mud. Around 60% of nests were degraded or predated. Predation was the main cause of egg loss. Successful nests (with chicks or hatching signs) represented 26% of the total nests monitored. This study reports the first information on the biometry of the species’ eggs and nests, confirming the northern coast of Rio de Janeiro state as a nesting area for the species.